Metal accumulation by Alyssum serpyllifolium subsp. malacitanum Rivas Goday (Brassicaceae) across different petrographic entities in Sou.th- Iberian ultramafic massifs: plant-soil relationships and prospects for phytomining. - Manteca Bautista, David; Pérez-Latorre, Andrés Vicente; Freitas, Helena; Hidalgo-Triana, Noelia (Taylor & Francis, 2022)
In the ultramafic area of Spain, a high quantity of petrographic entities is present. Data on the variability among populations of hyperaccumulation are scarce. We investigated Alyssum serpyllifolium subsp. malacitanum for variations in eleven elements among populations growing in different ultramafic massifs in different petrographic entities (dunites, harzburgite-pyroxenic dunite, harzburgite-lherzolite, pyroxenite, and serpentinites). Samples of leaves and soils were collected from the ultramafic outcrops of Sierra Bermeja and Sierra de Mijas (Andalusia, Spain). The concentrations of Ni, Fe, Mg, Si, Cr, Co, Sr, Mn, Cu, Zn, and Ba and the bioaccumulation factors (BAF) were determined. Although analysis of variance of the data for each element revealed considerable variation in soil chemistry (for Fe, Mg, Sr, and Ba) among the different petrographic entities, population-level variation with regard to the hyperaccumulation in the leaves was not detected. BAF values >1 were obtained for Sr and Ni depending on the petrographic entities. The correlation detected between the concentration of Ni in leaves and concentration in soil is relevant. The population-level variation obtained in the BAF values for Sr and Ni provides comprehensive information on the natural variation of hyperaccumulation. The BAF obtained for Ba is an important result for phytomining.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/5426?template=romeo
Keywords: Plantas - Efectos de los metales; Plantas hiperacumuladoras - Sierra Bermeja (Málaga); Hyperaccumulation; Alyssum; Bermeja; Mijas